Black-White variations in the lagged reciprocal relationship between religiosity and perceived control - Oates, Gary (Mental health, religion & culture, 2013)
This national longitudinal data-based multi-population LISREL study, the most comprehensive assessment to date of racial variations in the (in)congruity between religiosity and perceived control, gauges variation among Black and White Americans in the lagged reciprocal relationship between religiosity dimensions and mastery. Racial variation in the reciprocal religiosity-perceived control relationship has hitherto gone un-addressed. Prior investigations have also typically utilised cross-sectional samples - often from regional or age-specific populations. The observed public religiosity-mastery relationship over time exhibits signs of mutual reinforcement among Blacks: public religiosity enhances Blacks’ subsequent mastery, while prior mastery borderline-significantly enhances their public religiosity. The subjective religiosity-mastery relationship among Whites evinces a marginally countervailing pattern: Subjective religiosity diminishes Whites’ mastery, while mastery borderline-significantly enhances their subjective religiosity. The inordinately positive public religiosity-effect on Blacks’ mastery notably constitutes solid support for the "resource compensation" perspective on the impact of religiosity on mastery across dominant and subordinate groups.